Effectiveness of outrigger and belt truss systems on the seismic behaviorof high-rise buildings - Dedeoğlu, İbrahim Özgür; Calayır, Yusuf (My University, 2020)
The outrigger systems, which is widely used with shear wall-framed systems at the tall buildings, increase the lateral stiffness of the structural bearing system and reduce the lateral drift of the structure under lateral loads. However, the traditional outrigger systems, besides these positive contributions, also create some limitations and problems affecting the modeling of the structure. Some of these; more interior space occupying as an architect, problems arising in the connection of outrigger and center core (especially when a concrete shear-wall core is used). On the other hand, the belt trusses known as “Virtual Outriggers”which have recently been used to build high-rise structures, haveremovedthese problems. Unlike the traditional outrigger systems,belt trusses areformed between the outer columns. In this way belt trusses eliminate the problems arising from the direct connection of the outriggers to the center core and other problems associated with using outriggers. Extensive studies have been carried out on the examination of outrigger and belt truss systems used in high-rise buildings under static and dynamic loads. In this study, the linear earthquake responses of three structural models, which are shear wall-framed system, shear wall-framed system with traditional outriggers and shear wall-framed system with belt trusses, were performed by using modal time history analysis method. Lateral displacements and drifts of the structure, internal forces of the structural elements were obtained. These results of three structural models were compared with each other and the effectiveness of outrigger and belt truss systems were assessed. For earthquake input, three real earthquake records wereselected. These records were scaled in accordance with theDD2 level earthquake design spectrum defined in Turkish Building Earthquake Standards (2018) and used in the analyses.
Keywords: İnşaat Mühendisliği